Plugged-in: a Canadian survey of technology ownership, access, use, and attitudes among emergency department patients - Curtin Wach, Aisling; Joshi, Krutika; Seo, Christina; Wegier, Pete (Frontiers in Digital Health, 2025)
IntroductionPatient-facing digital health technologies have the capacity to remedy some of the challenges faced by overburdened and under-resourced Canadian emergency departments (ED). However, the successful implementation of such innovations is dependent on patients' willingness and ability to access and use digital technologies. Moreover, the potential presence of digital disparities in local communities may create or exacerbate inequitable health outcomes. This study aimed to understand technology ownership, access, use, and attitudes among ED patients of a digitally innovative hospital located in an ethnoculturally diverse, urban area of Toronto.MethodsAn electronic, self-report, cross-sectional survey was conducted in the ED of an urban, community hospital in Toronto. A convenience sample of ED patients over the age of 18 and proficient in English were invited to participate in the survey between January 3rd and February 14th, 2024. Participants responded to a battery of questions and scales (e.g., the Media and Technology Usage and Attitudes Scale; MTUAS) that were adapted as necessary for this study.ResultsThe final sample size of 250 participants had a mean age 40.4 ± 16 years, 64.4% were female, and 38% were born outside of Canada. Ownership of at least one digital device was high (97.6%), as was the use of smartphones (96.0%), email (93.6%), text messaging (94.8%), and internet searching (95.6%). Almost all participants had access to the internet (98.0%). Attitudes towards technology were generally positive (mean 4.2/5). There were no significant differences in technology ownership and use based on where participants lived. Few barriers to technology were reported.ConclusionDespite concerns of digital disparities in an ethnoculturally diverse area of Toronto, technology ownership, access, and use appear to be pervasive among ED patients, irrespective of where they reside. These findings, coupled with patients' generally positive attitudes towards technology, green-light the exploration of patient-facing digital health tools that utilize the digital technology ED patients already own, access, and use to improve the delivery of emergency care.